The Gαs‐protein‐mediated pathway may be steadily stimulated by prostanoid EP2 receptors, but not by EP4 receptors - Keijo Fukushima; Kanaho Senoo; Naoki Kurata; John W. Regan; Hiromichi Fujino (FEBS Open Bio, 2022)
EP2 and EP4 prostanoid receptors have long been considered to have similar roles, since they are known to couple with Gαs‐protein and activate cAMP‐mediated signaling pathways. In this study, we re‐evaluated the results of cAMP assays with or without phosphodiesterase (PDE) inhibitor pretreatment. Here, we show that in the absence of PDE inhibitor pretreatment, prostaglandin E2 causes accumulation of cAMP in EP2 receptors, whereas markedly low levels of cAMP accumulated in EP4 receptors. By applying the Black/Leff operational model calculation, we found that EP2 receptors have a biased ability to intrinsically activate the Gαs‐protein‐mediated pathway, whereas EP4 receptors have strong biased activity for the Gαi‐protein‐mediated pathway. Thus, EP2 and EP4 receptors may not be similar Gαs‐coupled receptors but instead substantially different receptors with distinct roles.